"The Way That I Look at Things [Is] Different Because It's Me": Constructing and Deconstructing Narratives About Racialized Sexual Selves. Issue 1 (15th May 2017) - Montemurro, Beth
Abstract : Many gender scholars have abandoned the notion that we can explore women's experiences without attention to other identities such as race, class, and/or sexual orientation. Until now, the ways race influences the development of sexual selves has been underexplored. In this paper, I focus on heterosexual women's accounts of the interplay of race, gender, and sexualities. Based on in‐depth interviews with sixty‐two white and African American heterosexual women between the ages of twenty and sixty‐eight, I examine the ways in which narrative work tells a story about the presentation of public sexual selves. I also explore how women's personal narratives are impacted by larger cultural narratives about race. Specifically, through a study of sexuality, I focus on the social construction of "postracialism."